Measurement and analysis of reversible transformations of vortex-free and singular light fields produced by PDLC cells - Ponevchinsky, V.V.; Vasil’ev, V.I.; Soskin, M.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
In this work, we have firstly realized and investigated reversible
transformations of vortex-free and singular optical complex landscapes appearing in a
He-Ne laser beam transmitted through a PDLC cell, which is controlled by an applied
DC voltage. Biaxes of all micro size LC domains are oriented approximately along the
applied electric field, and vortex-free complex landscape exists at 200 V. At 160 V,
biaxes orientation spreads, and the first ‘embryo’ of vortices in the form of a smooth
phase step appears. The first vortex pair nucleates at 140 V. Multitude of vortex pairs is
realized when electric field is switched off. Reversed evolution is realized when the
applied DC voltage grows from zero value to 200 V. It was shown that the observed
topological evolution is fully defined by changes in structure and localization of real and
imaginary zero-intensity lines for output complex light field. The developed technique of
parametric dynamics can be applied successfully to realize and investigate various types
of controlled optical elements including media with nanoadditions.